Chapter 1: Laygues: The Ambiguity in Witnessing. - Boulé, Jean-Pierre (HIV Stories: The Archaeology of AIDS Writing in France, 1985-1988, 2002)
Chapter 1 of the book "HIV Stories: The Archaeology of AIDS Writing in France, 1985-1988," by Jean-Pierre Boulé is presented. It explores the ambiguity in witnessing by a woman whose husband has contracted the AIDS. It highlights the book "Sida, Témoignage sur la vie et la mort de Martin," by Hélèn Laygues. It examines how the book has been classified into the category of AIDS writing under the title "AIDS and the Culture of Accompaniment in France."